PEMANFAATAN DAUN KELOR SEBAGAI UPAYA PENCEGAHAN KEJADIAN STUNTING PADA ANAK USIA PRA SEKOLAH DI TK ‘AISYIYAH 6 PADANG - Meta Rikandi; Asmeri Lamona; Weni Kurnia Sari (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Stunting is a chronic malnutrition problem caused by inadequate nutritional intake for a long time due to feeding that is not in accordance with nutritional needs. Stunting children is an indication of a lack of nutritional intake, both in quantity and quality that is not met.Ignorance of the benefits of Moringa leaves for health, due to lack of information about processing Moringa leaves into pudding for teachers and parents at TK Aisyiyah 6 Padang. Based on the results of the documentation study carried out by the service, the solution that will be offered to partners is education by taking steps to educate about the benefits of Moringa leaves and processing in the form of outreach activities / Counseling to teachers and parents of 'Aisyiyah 6 Padang Kindergarten students, distribution of Moringa plants , as well as processing Moringa leaves into Moringa pudding.From the results of the community service carried out, the following results were obtained: the knowledge of the Kindergarten teacher 'Aisyiyah 6 Padang had a good category (60%) about stunting and the use of Moringa leaves as an effort to prevent stunting in children. This study was a cross sectional study to determine the level of knowledge of TK 'Aisyiyah 6 Padang teachers about stunting and the use of Moringa leaves as an effort to prevent stunting in children. Based on the table above, it can be seen that the knowledge of the Kindergarten teacher 'Aisyiyah 6 Padang has a good category (60%) about stunting and the use of Moringa leaves as an effort to prevent stunting in children.